Pharmacologic modulation of 5-fluorouracil by folinic acid and high-dose pyridoxine for treatment of patients with digestive tract carcinomas - David Machover (Nature Portfolio, 2021)
Abstract Supplementation of cancer cells exposed to 5-fluorouracil (FUra) and folinic acid (FA) with high concentration pyridoxal 5′-phosphate, the cofactor of vitamin B6, potentiates the cytotoxicity of FUra in a synergistic interaction mode. We report a pilot study in 13 patients with previously untreated advanced carcinoma of the digestive tract to assess the impact of high-dose pyridoxine (PN) on the antitumor activity of regimens comprising FUra and FA. Five patients had colorectal adenocarcinoma (CRC); 5 had pancreas adenocarcinoma (PC); and 3 had squamous cell carcinoma of the esophagus (EC). Patients with CRC and with PC received oxaliplatin, irinotecan, FUra and FA, and patients with EC had paclitaxel, carboplatin, FUra and FA. PN iv from 1000 to 3000 mg/day preceded each administration of FA and FUra. Eleven patients responded. Two patients with CRC attained CRs and 3 had PRs with reduction rates ≥ 78%. Two patients with PC attained CRs, and 2 had PRs with reduction rates ≥ 79%. Responders experienced disappearance of most metastases. Of 3 patients with EC, 2 attained CRs. Median time to attain a response was 3 months. Unexpected toxicity did not occur. Results suggest that high-dose vitamin B6 enhances antitumor potency of regimens comprising FUra and FA.